Tracing evolution and communication dynamics in Chinese independent documentary films (2012-2022): a systematic review of genre, censorship, culture, and distribution - Wang, Anting; Osman, Mohd Nizam; Yasin, Megat Al-Imran; Mohd Hasan, Nurul Ain; Cui, Ying (Redfame Publishing, 2024)
In the last decade, Chinese independent documentaries have witnessed a profound transformation. While mainstream Chinese documentaries have been extensively examined in scholarly research, there remains a noticeable gap in the comprehensive analysis of independent documentaries from 2012 to 2022. This study employs a systematic literature review methodology to provide a holistic assessment of the evolution of Chinese independent documentaries during this pivotal period. It delves into various dimensions, encompassing the impact of political dynamics, funding mechanisms, the selection of film themes, ethical considerations, distribution challenges, and documentary filmmakers' perspectives. By conducting a rigorous qualitative analysis of approximately 47 scholarly articles from the specialized journal Chinese Independent Cinema Observer and the academic database Scopus, this research reveals the nuanced progression of independent documentaries within China's dynamic cultural, social, and political context. Preliminary insights from the selected research articles indicate a focused understanding and interest in societal hotspots and political censorship issues within independent documentaries. Furthermore, this research focuses on the unique challenges and opportunities encountered by Chinese independent documentaries during the phases of dissemination and reception. This study offers scholars a profound comprehension of the Chinese independent documentary landscape and provides invaluable strategic insights for producers and distributors.